Prudentia as becoming-shame: knowledge production in Southern Theory research Practice. Issue 1 (2nd January 2017) - Nye, Adele; Amazan, Rose; Charteris, Jennifer
Abstract: Over the last decade authors have critiqued the hegemonic structures that perpetuate knowledge hierarchies in the dominant research regimes that foster privilege across the globe. The authors in this article use collective biography to reflectively engage with knowledge production in the academy. They explore the nature of prudentia as an affective shame that surfaces through reflexive engagement with the politics of research cultures. Collective biography, as a 'grassroots' form of deliberate and collaborative interrogation, produces insight from 'difficult knowledge' that sheds light on power imbalance in North/South relations in research practice. In endeavouring to grapple with Southern Theory, the authors surface 'unwelcome truths'. These disquieting ruptures reveal the power of prudentia for academics who are desirous to unsettle the complacency of Northern assumptions as they engage in an ongoing struggle with doing Southern Theory.